Conceptualising centres of excellence: a scoping review of global evidence. Issue 2 (7th February 2022) - Manyazewal, Tsegahun; Woldeamanuel, Yimtubezinash; Oppenheim, Claire; Hailu, Asrat; Giday, Mirutse; Medhin, Girmay; Belete, Anteneh; Yimer, Getnet; Collins, Asha; Makonnen, Eyasu; Fekadu, Abebaw
Abstract : Objective: Globally, interest in excellence has grown exponentially, with public and private institutions shifting their attention from meeting targets to achieving excellence. Centres of Excellence (CoEs) are standing at the forefront of healthcare, research and innovations responding to the world's most complex problems. However, their potential is hindered by conceptual ambiguity. We conducted a global synthesis of the evidence to conceptualise CoEs. Design: Scoping review, following Arksey and O'Malley's framework and methodological enhancement by Levac et al and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Data sources: PubMed, Scopus, CINAHL, Google Scholar and the Google engine until 1 January 2021. Eligibility: Articles that describe CoE as the main theme. Results: The search resulted in 52 161 potential publications, with 78 articles met the eligibility criteria. The 78 articles were from 33 countries, of which 35 were from the USA, 3 each from Nigeria, South Africa, Spain and India, and 2 each from Ethiopia, Canada, Russia, Colombia, Sweden, Greece and Peru. The rest 17 were from various countries. The articles involved six thematic areas—healthcare, education, research, industry, information technology and general concepts on CoE. The analysis documented success stories of using the brand 'CoE'—an inﬂuential brand to stimulate best practices. We identified 12 essential foundations of CoE—specialised expertise; infrastructure; innovation; high-impact research; quality service; accreditation or standards; leadership; organisational structure; strategy; collaboration and partnership; sustainable funding or financial mechanisms; and entrepreneurship. Conclusions: CoEs have significant scientific, political, economic and social impacts. However, there are inconsistent use and self-designation of the brand without approval by an independent, external process of evaluation and with high ambiguity between 'CoEs' and the ordinary 'institutions' or 'centres'. A comprehensive framework is needed to guide and inspire an institution as a CoE and to help government and funding institutions shape and oversee CoEs.